Association of Vitamin D Deficiency in Pakistani Women with Polycystic Ovarian Syndrome - Sajida Munir Siddique, Sanobar Baloch, Nahil Shams, Kanta Bai Ahuja, Mariam Hafeez, Mir Mehrab Jan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Females suffering from polycystic ovarian syndrome have an increased likelihood of experiencing a deficiency in vitamin D. Methods: The Obstetrics and Gynecology department at Indus Medical College Tando Muhammad Khan, conducted a cross-sectional study for six months. The study aimed to investigate 160 women aged 17–44 who presented with the polycystic ovarian syndrome. The researchers collected blood samples from the participants and measured their vitamin D levels. If the serum levels of 25-hydroxyvitamin D3 were less than 20ng/ml, the participants were considered vitamin D deficient. The researchers obtained written informed consent from all participants and used SPSS version 20 to enter and analyze the collected data. Results: The study included patients aged between 17 and 44 years old, with an average age of 25.721 ± 7.56 years. The majority of patients (n=118, 73.7%) fell within the 17-30 age range, while 52 patients (26.0%) were between the ages of 32-45. In the study group, 74 patients (46.25%) were classified as obese. However, there was no significant contrast in the occurrence of vitamin D insufficiency among different age brackets (17-30 vs. 31-44 years) or body mass index classifications (overweight vs. non-overweight). Specifically, the percentages were 57.6% vs. 57.1% for age categories and 64.8% vs. 52.3% for body mass index divisions, correspondingly, with p-values of 0.643 and 0.045. Conclusion: Among females with polycystic ovary syndrome (PCOS), the prevalence of insufficient levels of vitamin D was determined to be 58.0%. Nonetheless, there were no significant differences in the occurrence of vitamin D insufficiency across different age and BMI groups. Keywords: Vitamin D deficiency, polycystic ovarian syndrome, obesity